APPLICATION OF THE RIGID FINITE ELEMENT METHOD TO MODELLING ROPES - KAMINSKI, HENRYK (2012)
TWO-DIMENSIONAL MOTION OF A ROPE FIXED AT ONE END IS CONSIDERED. THE RIGID FINITE ELEMENT METHOD (RFEM) IS REVIEWED AND APPLIED TO OBTAIN A MODEL OF THE ROPE, INCLUDING ITS ELASTIC AND DISSIPATIVE PROPERTIES. EQUATIONS OF MOTION ARE DERIVED WITHOUT THE SMALL DISPLACEMENT ASSUMPTION, USING THE LAGRANGE EQUATIONS. THE RESULTING MODEL IS COMPARED TO ANOTHER ONE, BEING DERIVED WITHIN THE FRAMEWORK OF STANDARD ANALYTICAL MECHANICS METHODS AND THE LAGRANGE FORMALISM. ADVANTAGES OF THE RFE APPROACH ARE DISCUSSED FROM A COMPUTATIONAL POINT OF VIEW. THE PRESENTED, ALTERNATIVE MODEL CAN BE A BASIS FOR EFFICIENT NUMERICAL SIMULATIONS, WHICH SEEM TO BE USEFUL IN FURTHER, COMPARATIVE STUDIES OF THE ROPE DYNAMICS.